Luseogliflozin and caloric intake restriction increase superoxide dismutase 2 expression, promote antioxidative effects, and attenuate aortic endothelial dysfunction in diet‐induced obese mice - Shigeru Kawade; Kazuma Ogiso; Sigfrid Casmir Shayo; Takahiko Obo; Aiko Arimura; Hiroshi Hashiguchi; Takahisa Deguchi; Yoshihiko Nishio (Journal of Diabetes Investigation, 2023)
Abstract Aims/Introduction The mechanisms underlying the effect of sodium‐glucose cotransporter 2 (SGLT2) inhibitors on aortic endothelial dysfunction in diet‐induced obesity are not clearly understood. This study investigated whether SGLT2 inhibition by luseogliflozin improved free fatty acid (FFA)‐induced endothelial dysfunction in high‐fat diet (HFD)‐induced obese mice. Materials and Methods Mice were fed a control diet or high‐fat diet for 8 weeks, and then each diet with or without luseogliflozin was provided for an additional 8 weeks under free or paired feeding. Afterward, the thoracic aortas were removed and utilized for the experiments. Results Luseogliflozin treatment decreased body weight, fasting blood glucose, insulin, and total cholesterol in HFD‐fed mice only under paired feeding but not under free feeding. Endothelial‐dependent vasodilation under FFA exposure conditions was significantly lower in HFD‐fed mice than in control diet‐fed mice, and luseogliflozin treatment ameliorated FFA‐induced endothelial dysfunction. Reactive oxygen species (ROS) production induced by FFA was significantly increased in HFD‐induced obese mice. Luseogliflozin treatment increased the expression of superoxide dismutase 2 (SOD2), an antioxidative molecule, and reduced FFA‐induced ROS production in the thoracic aorta. Superoxide dismutase reversed FFA‐induced endothelial dysfunction in HFD‐fed mice. Conclusions It was shown that caloric restriction is important for the effect of luseogliflozin on metabolic parameters and endothelial dysfunction. Furthermore, SGLT2 inhibition by luseogliflozin possibly ameliorates FFA‐induced endothelial dysfunction by increasing SOD2 expression and decreasing reactive oxygen species production in the thoracic aorta.